2015
DOI: 10.5657/fas.2015.0137
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze Activity in Temperate Fish from the East Sea, Korea

Abstract: Antifreeze proteins and glycoproteins [AF(G)Ps] constitute a group of proteins that lower the freezing but not the melting points of aqueous solutions, enabling polar and north-temperate fish to survive in ice-laden environments. However, little is known about antifreeze activity in temperate fish; such work would extend our knowledge on the functions and evolution of AF(G)Ps. In the present study, we screened for antifreeze activity in temperate fish caught off the coast of Jumunjin (37.89°N), Gangneung, Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Conversely, it is not likely that temperate and/ or subtropical fish require antifreeze activity for survival. However, contrary to our expectation, we observed antifreeze activity in some temperate and subtropical fish from the ice-free East Sea of Korea (Kim 2015). Among nine fish examined in that region, three fish, Gymnocanthus herzensteini, Zoarces gillii, and Kareius bicoloratus, exhibited antifreeze activity.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, it is not likely that temperate and/ or subtropical fish require antifreeze activity for survival. However, contrary to our expectation, we observed antifreeze activity in some temperate and subtropical fish from the ice-free East Sea of Korea (Kim 2015). Among nine fish examined in that region, three fish, Gymnocanthus herzensteini, Zoarces gillii, and Kareius bicoloratus, exhibited antifreeze activity.…”
Section: Introductioncontrasting
confidence: 99%
“…In addition, P. olivaceus did not initially demonstrate an antifreeze activity (Kim 2015). However, its EST analysis revealed that it carried a transcribable afp4 gene, which further raised the question of the function of this transcript.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these ndings, Gauthier et al (2008) speculated that ISP4 may not be a key antifreeze protein in the blood of polar sh when other types of antifreeze protein are present. Surprisingly, in addition to polar sh, ISP4 is also found in warm-temperate sh and freshwater sh (Nishimiya et al, 2008;Zhang et al, 2009;Kim, 2015;Lee and Kim, 2016). These reports indicate that ISP4 may have other effects as well as antifreeze activity in warm-temperate sh.…”
Section: Introductionmentioning
confidence: 99%